Pendekatan Problem Based Learning Model Diskusi Kelompok Berbantuan Video YouTube untuk Meningkatkan Aktivitas dan Hasil Belajar Statistika - Nugroho, Wachid (Universitas Islam Negeri Sunan Kudus, 2021)
Tujuan penelitian tindakan kelas ini untuk mengetahui peningkatan aktivitas dan hasil belajar statistika melalui pendekatan problem based learning (PBL) model diskusi kelompok berbantu video YouTube. Subjek penelitian ini adalah 24 siswa kelas XII pada salah satu Madrasah Aliyah di Salatiga. Data penelitian dikumpulkan melalui 1) pengamatan guru dan wawancara mengenai aktivitas belajar siswa; 2) pengisian lembar evaluasi diri siswa terhadap aktivitas belajar; dan 3) pre-tes dan tes tertulis 20 soal pilihan ganda di akhir siklus I dan II. Data pengamatan dan wawancara, lembar evaluasi diri siswa, serta penilaian belajar (pre-tes dan tes siklus I dan II) dianalisis secara deskripsi komparatif, baik kuantitatif maupun kualitatif pada aspek peningkatan aktivitas dan hasil belajar. Hasil penelitian menunjukkan persentase peningkatan keaktivan siswa 4,17% dari capaian siklus I (70,83%) ke siklus II (75,00%). Nilai rata-rata kelas meningkat 11,04 dari siklus I (62,71) ke siklus II (73,75). Sedangkan persentase ketuntasan kelas meningkat 25 % dari siklus I (54,17%) ke siklus II (79,17%). Temuan ini mengungkap pendekatan (PBL) model diskusi kelompok berbantu video YouTube dapat dijadikan alternatif untuk meningkatkan aktivitas dan hasil belajar statistika siswa. The purpose of this action research is to determine the increase in activity and learning outcomes of statistics through a problem based learning (PBL) approach to group discussion models assisted by YouTube videos. The subjects of this study were 24 students of class XII at one Madrasah Aliyah in Salatiga. Research data were collected through 1) teacher observations and interviews regarding student learning activities; 2) filling out student self-evaluation sheets on learning activities; and 3) pre-test and written test of 20 multiple choice questions at the end of cycles I and II. Observational and interview data, student self-evaluation sheets, and learning assessments (pre-test and test cycles I and II) were analyzed in a comparative description, both quantitatively and qualitatively in the aspect of increasing activity and learning outcomes. The results showed the percentage increase in student activity was 4.17% from the achievement of the first cycle (70.83%) to the second cycle (75.00%). The average value of the class increased by 11.04 from the first cycle (62.71) to the second cycle (73.75). While the percentage of class completeness increased by 25% from the first cycle (54.17%) to the second cycle (79.17%). These findings reveal that the YouTube video-assisted group discussion (PBL) approach can be used as an alternative to improve student statistics learning activities and outcomes.